The finch in the coal mine: Interrogating the environmental politics of extinction narratives. (8th September 2022) - Hine, Amelia; Mayes, Robyn; Hurst, Bree
Abstract: The black‐throated finch is an endangered species whose highest quality remaining habitat directly overlaps with the site of the controversial Adani Carmichael coal mine in Central Queensland, Australia. The image of this finch has been widely used by anti‐Adani protest groups as a powerful symbol for the destructive nature of greenfield coal mining. Drawing on extinction studies literature, we problematise the use of the black‐throated finch as a symbol of imminent extinction, highlighting how activists have constructed a fixed finch on‐the‐brink ontology that narrows possible futures for the species. We identify how the finch has been strategically deployed as an affective tool for engaging publics while the anti‐Adani campaign has been primarily driven by concerns around climate change futures. We use primary sources of anti‐Adani ephemera as well as interviews with key scientists, activists, and image‐makers involved in the debate about the Carmichael coal mine. We argue that critical evaluation of the effects and potential consequences of simplified environmental activist narratives and the instrumentalisation of nonhumans is needed to support and enable activism that centres care and responsibility within multispecies entanglements. Engagement with the complexities of environmental intervention in relation to the finch, and not exclusively the mine, is also necessary to locate openings through which more‐than‐human futures can be creatively imagined and enacted. Abstract : This article explores the instrumentalisation and ontological state of the black‐throated finch resulting from the development of a singular extinction narrative by the Stop Adani movement in Australia. By influencing public conversation around the species, this extinction narrative has implications for the finch's long‐term survival. We find that to undertake activism that centres care and responsibility discourses, it is necessary to avoid establishing a fixed species on‐the‐brink ontology and to resist a binary of industry versus species flourishing.